The Synthesis of N, N‐Bis(dialkoxyphosphinoylmethyl)‐ and N, N‐Bis(diphenylphosphinoylmethyl)glycine Esters by the Microwave‐Assisted Double Kabachnik–Fields Reaction. Issue 6 (31st October 2013) - Bálint, Erika; Fazekas, Eszter; Drahos, László; Keglevich, György
ABSTRACT The condensation of a glycine ester, two equivalents of paraformaldehyde, and the same quantity of a dialkyl phosphite or diphenylphosphine oxide afforded the title compounds as new bis(phospha‐Mannich) products under microwave (MW) conditions at 100°C. The dialkoxyphosphinoylmethyl derivatives were synthesized under solvent‐free conditions, whereas the diphenylphosphinoylmethyl derivatives were synthesized in acetonitrile solution. Comparative thermal experiments showed the beneficial role of MW in respect of efficiency.